PENINGKATAN MUTU PENDIDIKAN MADRASAH MELALUI IMPLEMENTASI STANDAR ISI DAN STANDAR PROSES PENDIDIKAN - Taufiq Ahmad (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2022)
Taufiq, NIM: 2112011000007, Program Magister of Islamic Religious Education, The Faculty of Tarbiya and Teaching Sciences “Effort to Improve the Quality of Learning Through Content Standards Implementation and Standards Education Process” (Case Study in MAN Serang City, Banten) The purpose of this study is divided into two general purpose and special purpose. The general objective of this study was to determine the quality improvement of education in MAN 2 Kota Serang along with the factors that influence it. While the purpose of this study was to reveal khsusus implementation of content standards and processes related to improving the quality of education in educational institutions of Islamic Madrasah Aliyah in Serang, Banten. This study will provide a clear picture based on the existing realities on improving the quality of education through the implementation of content standards and the educational. The focus of this research is to answer the question of: (1) How is the Implementation of Content Standards in MAN 2 Kota Serang, (2) How is Implementation Standards process at MAN 2 Kota Serang (3) How is the efforts to improve the quality of learning through the implementation of content standards and processes in Man 2 Serang city.This is a qualitative descriptive study. The design is a case study with a research setting conducted in Madrasah Aliyah Negeri (MAN) 2 Serang. With key informants such as Head of MAN 2, then another informant is chairman of the school committee, the head of the MDC (Madrasah Development Centre) and Head PENMA (madrasah education) Banten Province.Data were collected through interviews, documentation and observation. Based on the results of data analysis researchers obtained the following findings: (1) the implementation of education content standards in MAN 2 has been going well, according to conditions set by the government. (2) the implementation of the education process is going well, conducive, varied and innovative. (3) Efforts by the madrasah in improving the quality of learning by way of boarding school system and learning resource center (PSBB). Keywords: Content Standards, Process Standards, Quality Teaching, Madrasah.